A Violência doméstica contra a mulher no estado do Pará, no contexto da pandemia da covid-19 - PIEDADE, Ana Idalina Tenório (2022)
Abstract: The main purpose of the study was to analyze the domestic violence against women in the scope of the Covid-19 Pandemic. It is a qualitative research that used a bibliographic research related to the topic and the report of Brazilian Public Security Forum, correlated to violence against women in the period of social isolation between March and April 2020. Despite the quantitatives show that violence, during the social isolation, decreased, the feminicide numbers increased, forcing the responsible state agencies to take appropriate measures.